LIMT is a novel metastasis inhibiting lncRNA suppressed by EGF and downregulated in aggressive breast cancer. Issue 9 (3rd August 2016) - Sas‐Chen, Aldema; Aure, Miriam R; Leibovich, Limor; Carvalho, Silvia; Enuka, Yehoshua; Körner, Cindy; Polycarpou‐Schwarz, Maria; Lavi, Sara; Nevo, Nava; Kuznetsov, Yuri; Yuan, Justin; Azuaje, Francisco; et al.
Abstract: Long noncoding RNAs (lncRNAs) are emerging as regulators of gene expression in pathogenesis, including cancer. Recently, lncRNAs have been implicated in progression of specific subtypes of breast cancer. One aggressive, basal‐like subtype associates with increased EGFR signaling, while another, the HER2‐enriched subtype, engages a kin of EGFR. Based on the premise that EGFR‐regulated lncRNAs might control the aggressiveness of basal‐like tumors, we identified multiple EGFR‐inducible lncRNAs in basal‐like normal cells and overlaid them with the transcriptomes of over 3, 000 breast cancer patients. This led to the identification of 11 prognostic lncRNAs. Functional analyses of this group uncovered LINC01089 (here renamed LncRNA Inhibiting Metastasis; LIMT), a highly conserved lncRNA, which is depleted in basal‐like and in HER2‐positive tumors, and the low expression of which predicts poor patient prognosis. Interestingly, EGF rapidly downregulates LIMT expression by enhancing histone deacetylation at the respective promoter. We also find that LIMT inhibits extracellular matrix invasion of mammary cells in vitro and tumor metastasis in vivo . In conclusion, lncRNAs dynamically regulated by growth factors might act as novel drivers of cancer progression and serve as prognostic biomarkers. Synopsis: A long noncoding RNA, named LIMT, is downregulated by growth factors and accordingly expressed at low level in aggressive subtypes of breast cancer. LIMT inhibits metastasis in animals, possibly by reducing motility of cancer cell migration. EGF dynamically regulates the expression of lncRNAs. Expression of several EGF‐regulated lncRNAs correlates with clinical outcome of breast cancer patients. LIMT is an EGF downregulated lncRNA, which inhibits cell migration in vitro and metastasis in vivo . Aggressive, growth factor‐driven subtypes of breast cancer express relatively low levels of LIMT. Abstract : A long noncoding RNA, named LIMT, is downregulated by growth factors and accordingly expressed at low level in aggressive subtypes of breast cancer. LIMT inhibits metastasis in animals, possibly by reducing motility of cancer cell migration.